Toxocara cati and Other Parasitic Enteropathogens: More Commonly Found in Owned Cats with Gastrointestinal Signs Than in Clinically Healthy Ones - Aurora L. Ursache; Adriana Györke; Viorica Mircean; Mirabela O. Dumitrache; Andrei Răzvan Codea; Vasile Cozma (Pathogens, 2021)
Intestinal parasites are involved in the health and wellbeing of cats and some of them, due to their zoonotic potential, represent a problem for public health. This study aimed to assess the prevalence of parasitic infections in cats with gastrointestinal signs. Fecal samples collected from 137 cats were analyzed by the flotation method using a sodium chloride saturated solution. The overall prevalence of intestinal parasites was 50.4%. Intestinal parasites were significantly (p < 0.0001) more common in cats with digestive clinical signs (66.7%) than in clinically healthy ones (19.2%). Toxocara cati (40.2%) was the most frequently identified intestinal parasite, followed by Cystoisospora spp. (10.2%), hookworms (3.7%), Taeniidae (2.2%), Giardia duodenalis (2.2%), and Toxoplasma gondii (0.7%). Toxocara cati (53.3%, p < 0.0001) and Cystoisospora spp. (15.6%, p < 0.001) were significantly more frequently diagnosed in cats with clinical signs. A lack of deworming in the last three months (OR: 15.9), outdoor access (OR: 13.8), the presence of digestive symptoms (OR: 5.4), and young age (OR: 4.2) were identified as risk factors for T. cati infection by logistic regression analysis. Regardless of age, gastrointestinal signs like vomiting, diarrhea, and inappetence were positively associated with T. cati.